Combination of 35-Gene Mutation Profile and Radiotherapy Dosimetry Predicts the Therapeutic Outcome of Definitive Chemoradiation in Patients With Esophageal Squamous Cell Carcinoma - Tang, Peng; Tan, Chen; Pang, Qingsong; Chi, Chih-Wen; Wang, Yuwen; Yuan, Zhiyong; Huang, Yu-Chuen; Chen, Yu-Jen (Frontiers in Oncology, 2021)
Esophageal cancer is a common malignancy worldwide and is a leading cause of cancer-related mortality. Definitive concurrent chemoradiotherapy (CCRT) has been widely used to treat locally advanced esophageal squamous cell carcinoma (ESCC). In this study, we evaluated the predictive power of 35-gene mutation profile and radiation parameters in patients with ESCC. Data of 44 patients with ESCC who received definitive CCRT were retrospectively reviewed. A 35-gene mutation profile, derived from reported ESCC-specific next-generation sequencing results, and radiation dosimetry parameters were examined using the Kaplan–Meier curve and Cox proportional hazards model. All patients were native Chinese and received CCRT with a median follow-up time of 22.0 months. For progression-free survival, significant prognostic factors in the multivariable Cox regression model were clinical nodal staging ≥2 (HR: 2.52, 95% CI: 1.15–5.54, p=0.022), ≥10% lung volume receiving ≥30 Gy (V30) (HR: 2.36, 95% CI: 1.08–5.17, p=0.032), and mutation of fibrous sheath interacting protein 2 (FSIP2) (HR: 0.08, 95% CI: 0.01–0.58, p=0.013). For overall survival, significant prognostic factors in the multivariable Cox regression model were ≥10% lung volume receiving ≥30 Gy (V30) (HR: 3.71, 95% CI: 1.48–9.35, p=0.005) and mutation of spectrin repeat containing nuclear envelope protein 1 (SYNE1) (HR: 2.95, 95% CI: 1.25–6.97, p=0.014). Our cohort had higher MUC17 (79.5% vs. 5.7%), FSIP2 (18.2% vs. 6.2%), SYNE1 (38.6% vs. 11.0%) mutation rates, and lower TP53 (38.6% vs. 68.7%) mutation rates than the ESCC cohorts from The Cancer Genome Atlas data. In conclusion, using a combination of 35-gene mutation profile and radiotherapy dosimetry, the mutations of FSIP2 and SYNE1 as well as lung V30 were identified as potential predictors to develop a prediction model for clinical outcomes in patients with ESCC receiving definitive CCRT.